Histopathological subgroups in knee osteoarthritis - Wyatt, L.A.; Morerton, B.J.; Mapp, Paul I.; Wilson, D.; Hill, R.; Ferguson, Eamonn; Scammell, Brigitte E.; Walsh, David A. (Elsevier, 2016)
Objective: Osteoarthritis (OA) is a heterogeneous, multi-tissue disease. We hypothesised that different histopathological features characterise different stages during knee OA progression, and that discrete subgroups can be defined based on validated measures of OA histopathological features.